Implementation Of The Teaching Factory Learning Model In Improving Students' Competence At State Vocational High School 1 Pacet - Ende Junaedi; Sri Setyaningsih; Eka Suhardi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to obtain a fact-based picture in the form of data and information regarding the implementation of the Teaching Factory learning model at SMK Negeri 1 Pacet. Qualitative research methods are used to produce a comprehensive presentation based on findings in the field. The efforts made in education are on the learning processes and models used to achieve educational goals. Vocational High Schools (SMK) are schools that aim to prepare students who are skilled and ready to enter the world of work. To realize this goal, one of the flagship programs is the Teaching Factory. Teaching Factory is an effort to present the real world of work in an educational environment. The objectives of this Teaching Factory are (a) increasing the competency of students (b) increasing the entrepreneurial spirit of graduates (c) producing value-added products (goods/services) (d) expanding the scope of recruitment opportunities for vocational school graduates, and (e) increasing collaboration with the business/industrial world. KBased on the results of the research, it can be concluded that the implementation of Teaching Factory learning at SMK Negeri 1 Pacet on the Agribusiness Food Crops and Horticulture skills competency has gone well and can produce superior products and has been accepted as an industry standard by the market so that it can be used as a reference for other schools to implement Teaching Factory learning.